CARACTERIZAÇÃO DE SISTEMAS FOTOVOLTAICOS HÍBRIDOS A BASE DE ÓXIDO DE ZINCO - MAIA, GUILHERME ARIELO RODRIGUES (2017)
Technological advances require researches in clean and renewable energy sources to replace the fossil fuel. Inorganic/organic hybrid solar cells appear as an alternative to obtain photovoltaic solar energy. Hybrid solar cells of semiconductor oxides and conductive polymers have been broadly studied. Poly(3-alkylthiophene), P3AT, is an organic polymer formed by conjugated structures with conductive properties, photoluminescence, a relatively high charge mobility and stability. Zinc oxide (ZnO) has been used as an electron acceptor in this cell type because it offers great electron transport properties, simple manufacturing techniques, non-toxicity, variation and morphologic control. Different ZnO morphologies allow distinct properties in terms of electronic transport in solar cell interfaces. The objective of this work was to evaluate whether ZnO with its different morphologies can improve the anchorage of poly (3-hexylthiophene) P3HT and poly (3-octylthiophene) P3OT and investigates the conductive properties of ZnO/P3HT and ZnO/P3OT hybrid solar cells. ZnO particles were synthesized by the coprecipitation method with Zn(NO3)2.6H2O. The characterization techniques used were X-ray diffraction (XRD), Raman, FTIR, scanning electron microscopy (SEM), UV-vis, thermogravimetric analysis and differential scanning calorimetry (TG/DSC). Cells composed the working electrode (ZnO/P3AT) were evaluated by open circuit potential (Voc), electrochemical impedance spectroscopy (EIS) and photochronoamperometry. The SEM images showed 3 morphologies: spherical ZnO (E), hexagonal ZnO (H) and ZnO without defined morphology (M) due to the variation of the precursor salt concentration. Cells with different morphologies presented medium values of Voc = -0.438 ± 0.027 V. EIS indicated that the M/P3OT cell has lower resistance to the transfer of charge and high capacitances to the intermediate frequencies. The M/P3OT and M/P3HT solar cells presented the best results in relation to the electron transfer process, reaching the efficiency of 1.1 ± 0.12%.